Confirmation of TENM3 involvement in autosomal recessive colobomatous microphthalmia. Issue 7 (22nd April 2016) - Chassaing, Nicolas; Ragge, Nicola; Plaisancié, Julie; Patat, Oliver; Geneviève, David; Rivier, François; Malrieu‐Eliaou, Claudie; Hamel, Christian; Kaplan, Josseline; Calvas, Patrick
Abstract : Anophthalmia and microphthalmia are the most severe malformations of the eye, referring to a congenital absence, and a reduced size of the eyeball respectively. More than 20 genes have been shown to be mutated in patients with syndromic and non‐syndromic forms of anophthalmia–microphthalmia. In a recent study combining autozygome and exome analysis, a homozygous loss of function mutation in TENM3 (previously named ODZ3 ) was reported in two siblings with isolated bilateral colobomatous microphthalmia from a consanguineous Saudi family. Herein, we report a third patient (not related to the previously reported family) with bilateral colobomatous microphthalmia and developmental delay in whom genetic studies identified a homozygous TENM3 splicing mutation c.2968‐2A>T (p.Val990Cysfs*13). This report supports the association of TENM3 mutations with colobomatous microphthalmia and expands the phenotypic spectrum associated with mutations in this gene. © 2016 Wiley Periodicals, Inc.